2017
DOI: 10.5194/hess-2016-566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainty analysis of hydrological return period estimation, taking the upper Yangtze River as an example

Abstract: Abstract. Return period estimation plays an important role in the engineering practices of water resources and disaster 10 management, but uncertainties accompany the calculation process. Based on the daily discharge records at two gauging stations (Cuntan and Pingshan) on the upper Yangtze River, three sampling methods (SMs; (annual maximum, peak over threshold, and decadal peak over threshold), five distribution functions (DFs; gamma, Gumbel, lognormal, Pearson III, and general extreme value), and three para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…These are mainly spatial interpolation and map algebra methods. The natural neighbor method (e.g., Sibson 1981; Van der Graaf 2016) is applied for modeling of water surface spatial distribution. The conditional method for raters and reclassification is applied to properly process the interpolation results.…”
Section: Tools Of Spatial Analysismentioning
confidence: 99%
“…These are mainly spatial interpolation and map algebra methods. The natural neighbor method (e.g., Sibson 1981; Van der Graaf 2016) is applied for modeling of water surface spatial distribution. The conditional method for raters and reclassification is applied to properly process the interpolation results.…”
Section: Tools Of Spatial Analysismentioning
confidence: 99%
“…The hydrological community has identified the propagation of uncertainty as one of the 23 unsolved problems in hydrology (Blöschl et al, 2019). Numerous actors in water resource and hydrologic research have attempted to identify different sources of uncertainty in water resources (Kusangaya et al, 2018;Prein, 2019;Vetter et al, 2017;Xu et al, 2010) and extreme hydrological frequencies (Her et al, 2019;Qi et al, 2016;Sun et al, 2017;Vrugt et al, 2008;Zhang et al, 2016). These research works have addressed uncertainty in water resources and extreme hydrological modeling in the isolated form.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sun et al (2017) identified multiple sources of uncertainty (distribution types, distribution parameters, and peak over threshold) in flood frequency. They found that distribution types could play a significant role in controlling the flood magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There, rather simple analytical and bootstrap methods allow the exploration of the uncertainty of extreme quantiles. In a univariate framework, the effect of the choice of the marginal distribution (Merz & Thieken, 2005;Qi et al, 2016), parameter uncertainty of the marginal distribution (Qi et al, 2016), data uncertainty from threshold selection (Qi et al, 2016;Xu et al, 2010), and the effect of the choice of annual maxima sampling versus peakover-threshold sampling (e.g., Madsen et al, 1997;Martins & Stedinger, 2001a, 2001bSun et al, 2017) have been considered. In a bivariate framework that allows for the joint consideration of peak discharges and hydrograph volumes, the effect of the choice of annual maxima sampling versus peak-over-threshold sampling has, to our knowledge, not yet been analyzed.…”
Section: Introductionmentioning
confidence: 99%